Factors associated with applying to graduate/professional degrees for students engaged in undergraduate research experiences at minority serving institutions - Echegoyen, Lourdes E.; Mehta, Kala M.; Hueffer, Karsten; Chavira, Gabriela; Kagey, Jacob D.; Keller, Thomas E.; Morgan, Kathleen M.; Aley, Stephen B.; Chun, Chi-Ah; Sheikhattari, Payam; Wagler, Amy (Frontiers in Education, 2025)
IntroductionThis study investigates the impact of undergraduate research experiences on applications to graduate and professional programs, particularly for underrepresented minority students at Minority Serving Institutions (MSIs).MethodsThe study analyzes data collected at 10 MSIs participating in the NIH BUILD program to understand the relationship between research participation (in formal programs vs. informal research), student demographics, science self-efficacy, GPA, and application to advanced degree programs.ResultsResults indicate that undergraduate research participation, especially in formal programs for extended periods of time, positively influences applications to graduate/professional programs, with similar outcomes observed across underrepresented minority and non-minority students.DiscussionFindings indicate that organized programs in biomedical research training significantly increase the probability of students applying to graduate or professional programs when programs span more than 12 months. This has implications for the design and implementation of biomedical research training programs, especially at MSIs.